Sapiens [compact disc, unabridged] : a brief history of humankind - Harari, Yuval N. (Tantor Media, Inc., 2015)
"One hundred thousand years ago, at least six human species inhabited the earth. Today there is just one. Us. Homo sapiens. How did our species succeed in the battle for dominance? Why did our foraging ancestors come together to create cities and kingdoms? How did we come to believe in gods, nations, and human rights; to trust money, books, and laws; and to be enslaved by bureaucracy, timetables, and consumerism? Bold, wide-ranging, and provocative, Sapiens integrates history and science to challenge everything we thought we knew about being human: our thoughts, our actions, our heritage . . . and our future" --